Web-Based Inventory and Sales Information System: Indonesian Micro Small Medium Enterprise Case Study - Kevina Angellin; Raymond Sunardi Oetama; Mahfudz Amri (JOINS (Journal of Information System), 2023)
Information systems have a very important role in increasing productivity values that provide effectiveness and efficiency in the business sector. Cik Cik MSME Meatshop and Frozenfood is still using a manual system for recording their inventory and sales data, which causes several problems such as human error, human fraud, and inaccurate data. To overcome the problems, a solution is provided, that is a web-based information system, focused on the inventory and sales business processes. The information system is designed using Rapid Application Development method. The tools used are XAMPP as a web server and Visual Studio Code as a code editor. The programming language to be used is PHP, CodeIgniter as a framework, and MySQL as a database storage. The results obtained from the development of this information system are this system can help Cik Cik MSME Meatshop and Frozenfood in overcoming problems related to sales and inventory become easier to manage the data so that it is more automated compared to the previous manual system.